Strategi Kualitas Pelayanan dalam Membentuk Keputusan Nasabah Menggunakan Produk Tabungan Wadiah di BSI KCP Probolinggo Kraksaan - Ahmad Febriyanto; Aulia Izzatul Manghfiroh (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to understand the service strategy of Bank Syariah Indonesia (BSI) KCP Probolinggo Kraksaan in increasing customer satisfaction and decisions, especially on Easy Wadiah savings products. The approach used is qualitative phenomenology with interview, observation, and documentation methods to identify the main themes in the bank's service strategy. Data triangulation is applied to ensure the validity of the findings. The results of the study indicate that optimal service contributes significantly to increasing the number of customers. Ease of transaction process and responsiveness to customer needs build trust that drives customer decisions to choose sharia banking products. In addition, the Easy Wadiah savings marketing strategy applies the 4P and 7P marketing mix in various BSI branches. Product and price elements are the main attractions for customers. Digital-based marketing strategies through social media such as WhatsApp Business, Instagram, and the BSI Mobile Banking application have proven effective in increasing customer satisfaction. With competitive services, BSI KCP Probolinggo Kraksaan is able to compete with conventional banks and attract more customers. In conclusion, BSI's success in increasing the number of customers is highly dependent on optimal service strategies and innovative digital marketing.